ORP4L Facilitates Macrophage Survival via G-Protein–Coupled Signaling: ORP4L−/− Mice Display a Reduction of Atherosclerosis. Issue 12 (9th December 2016) - Zhong, Wenbin; Pan, Guoping; Wang, Lin; Li, Shiqian; Ou, Jingsong; Xu, Mengyang; Li, Jiwei; Zhu, Biying; Cao, Xiuye; Ma, Hongling; Li, Chaowen; Xu, Jun; et al.
Abstract : Rationale: : Macrophage survival within the arterial wall is a central factor contributing to atherogenesis. Oxysterols, major components of oxidized low-density lipoprotein, exert cytotoxic effects on macrophages. Objective: : To determine whether oxysterol-binding protein–related protein 4 L (ORP4L), an oxysterol-binding protein, affects macrophage survival and the pathogenesis of atherosclerosis. Methods and Results: : By hiring cell biological approaches and ORP4L − /− mice, we show that ORP4L coexpresses with and forms a complex with Gαq/11 and phospholipase C (PLC)-β3 in macrophages. ORP4L facilitates G-protein–coupled ligand-induced PLCβ3 activation, IP3 production, and Ca 2+ release from the endoplasmic reticulum. Through this mechanism, ORP4L sustains antiapoptotic Bcl-XL expression through Ca 2+ -mediated c-AMP responsive element binding protein transcriptional regulation and thus protects macrophages from apoptosis. Excessive stimulation with the oxysterol 25-hydroxycholesterol disassembles the ORP4L/Gαq/11 /PLCβ3 complexes, resulting in reduced PLCβ3 activity, IP3 production, and Ca 2+ release, as well as decreased Bcl-XL expression and increased apoptosis. Overexpression of ORP4L counteracts these oxysterol-induced defects. Mice lacking ORP4L exhibit increased apoptosis of macrophages in atherosclerotic lesions and a reduced lesion size. Conclusions: : ORP4L is crucial for macrophage survival. It counteracts the cytotoxicity of oxysterols/oxidized low-density lipoprotein to protect macrophage from apoptosis, thus playing an important role in the development of atherosclerosis. Abstract : Supplemental Digital Content is available in the text.